Raman spectroscopy and Raman optical activity of blood plasma for differential diagnosis of gastrointestinal cancers - Kralova, Katerina; Vrtelka, Ondrej; Fouskova, Marketa; Hribek, Petr; Bunganic, Bohus; Miskovicova, Michaela; Urbanek, Petr; Zavoral, Miroslav; Petruzelka, Lubos; Habartova, Lucie; Setnicka, Vladimir (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2024)
Improving the early diagnosis of gastrointestinal cancers is a crucial step in reducing their mortality. Given the non-specificity of the initial symptoms, the ability of any diagnostic method to differentiate between various types of gastrointestinal cancers also needs to be addressed. To detect disease-specific alterations in biomolecular structure and composition of the blood plasma, we have implemented an approach combining Raman spectroscopy and its conformation-sensitive polarized version, Raman optical activity, to analyze blood plasma samples of patients suffering from three different types of gastrointestinal cancer - hepatocellular, colorectal and pancreatic. First, we aimed to discriminate any type of gastrointestinal cancer from healthy control individuals; inthenext step, the focus was on differentiating among the three cancer types studied. The more straightforward of the two statistical approaches tested, the combination of linear discriminant analysis and principal component analysis applied to the entire spectral dataset, allowed the discrimination of cancer and control samples with 87% accuracy. The three gastrointestinal cancers were classified with an overall accuracy of 76%. The second method, the linear discriminant analysis applied to a selection of spectral bands, yielded even higher values. Cancer and control samples were distinguished with 89% accuracy and hepatocellular, colorectal and pancreatic cancer with an overall accuracy of 87%. The results obtained in our study suggest that the proposed approach may become a disease-specific diagnostic tool in daily clinical practice.
Keywords: analýza hlavních komponent; krevní plazma; gastrointestinální nádory; Hepatocellular carcinoma; Humans; diferenciální diagnóza; Blood plasma; Ramanova spektroskopie; Diagnosis, Differential; lidé; Optical Rotation; Principal Component Analysis; kolorektální nádory; Raman spectroscopy; optická otáčivost; Plasma; Spectrum Analysis, Raman; Colorectal cancer; Gastrointestinal Neoplasms; diskriminační analýza; Raman optical activity; Discriminant Analysis; Pancreatic cancer; Colorectal Neoplasms